Kontribusi Al Ghozali Dalam Dunia Pendidikan - Munasib Syihad (JIE (Journal of Islamic Education), 2016)
The Indonesia education system has many problems which ae caused by the existence of the unclear aims of national education. It is indicated by the moality degredation among the Indonesians, such as corruption, horizontal problemsamong the people, and the quality of the education. This one is maked by there is not any exact education taget. Moreover, the clear cut is the morality and self identity among the Indon peserta didiknya. Esian people. This article eveals the solutions of the problems by considering the idea ao Al – Ghazali’s education perspective. This suggest that the main objective of education’ thought is by placing the morality as the irst font. It is taken because the morality presents and shapes the people and their life’ thought. It determines the people’s life in attaining the well life.